Protocol and participatory engagement strategy for acommunity-based research route focused on locally led adaptation capacities - Rodriguez, Luz Angela; Herrera, Johana; Soler, Andres; Vanegas Cubillos, Martha; Alvarez, Javier; Zuleta, Santiago (2025)
The municipality of La Montañita, in the department of Caquetá, part of the Colombian Amazon, is a predominantly rural area characterized by Amazonian hill landscapes, Andean foothills, and alluvial valleys, where smallholder agri-food systems coexist with highly fragmented remnants of natural forest. From a socio-ecological systems perspective, we explore how the spatial configuration of the territory—including land cover distribution, water networks, rural property structures, and the location of climate- and human-induced threats—shapes both climate vulnerability and local capacities for adaptation. In addition, we analyze the use of agrobiodiversity and its adaptation potential, and we report on the co-design of a community-based action-research route to strengthen locally led adaptation capacities.